Monotheistic Hindus, Idolatrous Muslims: Muḥammad Qāsim Nānautvī, Dayānanda Sarasvatī, and the Theological Roots of Hindu–Muslim Conflict in South Asia - Naeem, Fuad S. (Religions (Basel, Switzerland ), 2025)
Contrary to popular notions of a perpetual antagonism between ‘Hinduism’ and ‘Islam’, played out on Indian soil over the centuries, this article examines the relatively recent origins of a Hindu–Muslim conflict in South Asia, situating it in the reconfigurations of ‘religion’ and religious identity that occurred under British colonial rule in the nineteenth and twentieth centuries. The multivalent and somewhat fluid categories of religious identification found in pre-modern India gave way to much more rigid and oppositional modern and colonial epistemic categories. While much has been written on how colonial policies and incipient Hindu and Muslim nationalisms shaped the contours of modern Hindu–Muslim conflict, little work has been done on the important role religious actors like Muslim and Hindu scholars and reformers played in shaping the discourse around what constituted Hinduism and Islam, and the relationship between the two, in the modern period. This study examines the first-known public theological debates between a Hindu scholar and a Muslim scholar, respectively, Swami Dayānanda Sarasvatī (1824–1883), founder of the reformist Arya Samaj and first exponent of a Hindu polemic against other religions, and Mawlānā Muḥammad Qāsim Nānautvī (1832–1880), co-founder of the seminary at Deoband and an important exponent of Islamic theological apologetics in modern South Asia, and how they helped shape oppositional modern Hindu and Muslim religious theologies. A key argument that Nānautvī contended with was Dayānanda’s claim that Islam is idolatrous, based on the contention that Muslims worship the Ka’ba, and thus, it is not a monotheistic religion, Hinduism alone being so. The terms of this debate show how polemics around subjects like monotheism and idolatry introduced by Christian missionaries under colonial rule were internalized, as were broader colonial epistemic categories, and developed a life of their own amongst Indians themselves, thus resulting in new oppositional religious identities, replacing more complex and nuanced interactions between Muslims and followers of Indian religions in the pre-modern period.